2018
DOI: 10.1016/j.jbusres.2018.01.027
|View full text |Cite
|
Sign up to set email alerts
|

The role of emotions and conflicting online reviews on consumers' purchase intentions

Abstract: Drawing on dual-process theories, this paper explains how the systematic and heuristic information processing of online reviews with conflicting information can influence consumers' purchase decision making. The study adopts major assumptions of complexity and configuration theory in employing fuzzy-set qualitative comparative analysis on 680 TripAdvisor users to test the complex interrelationships between emotions and the systematic and heuristic cues used in processing reviews. The results show that the syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(108 citation statements)
references
References 47 publications
5
101
0
2
Order By: Relevance
“…It is proposed that data are generalisable beyond the research setting if phenomena are examined across multiple units, and if one of units has similar conceptual foregrounds to other contexts (Maxwell, 2013;Yin, 2014). However, the advent of the Internet acknowledges the influence that online customers have on the perception constructs of others (Weitzl & Hutzinger, 2017;Ruiz-Mafe et al, 2018;Zhuang et al, 2018), posing the similarity that Kosovoan and Albanian online banking customers have to those of other contexts.…”
Section: Sampling Techniquementioning
confidence: 99%
“…It is proposed that data are generalisable beyond the research setting if phenomena are examined across multiple units, and if one of units has similar conceptual foregrounds to other contexts (Maxwell, 2013;Yin, 2014). However, the advent of the Internet acknowledges the influence that online customers have on the perception constructs of others (Weitzl & Hutzinger, 2017;Ruiz-Mafe et al, 2018;Zhuang et al, 2018), posing the similarity that Kosovoan and Albanian online banking customers have to those of other contexts.…”
Section: Sampling Techniquementioning
confidence: 99%
“…eWOM is considered as an important source of information influencing human behaviour (Filieri et al 2018;Filieri 2015;Floyd et al 2014;Nam et al 2018;Wang et al 2015a;Yan et al 2015), significantly affecting the way consumers make purchase decisions (Baber et al 2016;Jeong and Koo 2015;Lee et al 2017;Lin et al 2018;Mauri and Minazzi 2013). In recent studies, 93% of consumers indicated that online reviews (a type of eWOM communication) significantly influence their purchase decision (Fullerton 2017;Ruiz-Mafe et al 2018;Tata et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In this work, ORH reflects the capability of a review to enable other consumers to better understand the performance and quality of a product or a service [71]. Perceived helpfulness relates to how potential customers perceive a peer-generated evaluation of a product, service, or brand as valuable and useful in their purchasing decision process [124]. The profusion and multiplication of ORs makes information about products and services easy to find but somehow difficult to process and judge, thus increasing cognitive costs [14].…”
Section: Orh and Financial Performancementioning
confidence: 99%